IMPLEMENTASI OUTSOURCING STRATEGY PADA INDUSTRI ROKOK SIGARET KRETEK MESIN - Idris Idris (Faculty of Economics and Business Diponegoro University, 2013)
Many concepts and methods of efficiency have been developed recently. Ones is outsourcing strategy. It gives strategic benefit, however outsourcing have strategic risk. To be survive in global competition, Ciggarete Industry must make its production efficiently by outsourcing. Its uses the strategy to keep its machine and equipment. This research uses qualitative approach and case study Ciggarete Industry. By analyzing value chain at first, the research continue to identifying internal and external factor and making outsourcing decision. There are three type of outsourcing sequentially which can be used to make decision i.e. : (1) Strategic Vulnerability and Control Consideration Model, (2) Make or Buy Cost Analysis, and (3) Strategic Sourcing Model. Keywords :Outsourcing